The issues of old and new lexicography. Applied study: (S A F) material as a case study - Kheder, Lena Akram (Journal of Humanities & Social Sciences, 2020)
A variety of approaches were adopted by authors of Arabic dictionaries in which they paid attention to defining, labelling and ordering the lexical units. However, the confusion is evident in much of what they presented. This study aims at clarifying the aspects of confusion in the approach used in lexical authoring, and the standard adopted in examining the lexical units through studying (S A F) material in three dictionaries, namely: al- Qamus al- Muheet for al- Fayruzabadi (817 AH), Mujam Lesan al- Arab for Ibn Manzur (1311 AH) and al- Mujam al- Waseet, published in (1860 CE) by the Arabic Language Academy in Cairo. To this end, the paper adopted the descriptive and analytical method by tracking the material chosen in the previous dictionaries to show the standard adopted by authors of the dictionary in defining, ordering and labelling the lexical units, and to indicate the effectiveness of what they have provided in the field of lexicography.The study focuses on four main sections during the process of examination: the lexical definition, the internal arrangement under the lexical entry, the methodology of abbreviation appearance and the supporting definition elements; pattern, example and photo.
Keywords: lexical industry; lexical unit; definition; order; marking